1969
DOI: 10.1007/bf02533185
|View full text |Cite
|
Sign up to set email alerts
|

The enzymic synthesis of ganglioside: I. Brain uridine diphopphate D‐galactose: N‐acetyl‐galactosaminyl‐galactosyl‐glucosyl‐ceramide galactosyl transferase

Abstract: An enzyme which catalyzes the transfer of galactose from UDP‐galactose to galNAc‐gal‐glc‐ceramide is described. The enzyme is found mainly in the nervous tissue of tadpole (Taylor and Kollros stage 17), adult frog, adult and 8 day old rat. The enzymic activity is localized in the 11,500 xg, 20,000 xg and 100,000 xg particles. The UDP‐galactose: galNAc‐gal‐glc‐ceramide from the particles by treatment with sodium desoxylcholate and Triton X‐100. The pH optimum for the solubilized enyme is between 6.8 and 7.0 in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

1971
1971
1984
1984

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(6 citation statements)
references
References 22 publications
0
6
0
Order By: Relevance
“…In the present study we also observed that the concentrations of higher ganglioside homologues with migration of GMl, GDlb, GD16 and GT correlated positively with sensitivity of target cells to NK-cell-mediated lysis. These observations on the presence of asialo G, , G, , GDla, GDlb in NK-sensitive target cells suggest the existence of the alternate pathway for ganglioside biosynthesis (CM + CD + asialo G, + G, + GMl + GDla -+ GDlb + GT) (Handa and Burton, 1969;Yip and Dain, 1969;Yogeeswaran and Stein, 1980). In contrast, NK-insensitive targets lack asialo-G,, suggesting the presence of the classical pathway for the ganglioside biosynthesis (CM GT) which may be operative in these cell lines.…”
Section: Ir; 5 A9ht; 6 Yac-wa9ht; 7mentioning
confidence: 92%
“…In the present study we also observed that the concentrations of higher ganglioside homologues with migration of GMl, GDlb, GD16 and GT correlated positively with sensitivity of target cells to NK-cell-mediated lysis. These observations on the presence of asialo G, , G, , GDla, GDlb in NK-sensitive target cells suggest the existence of the alternate pathway for ganglioside biosynthesis (CM + CD + asialo G, + G, + GMl + GDla -+ GDlb + GT) (Handa and Burton, 1969;Yip and Dain, 1969;Yogeeswaran and Stein, 1980). In contrast, NK-insensitive targets lack asialo-G,, suggesting the presence of the classical pathway for the ganglioside biosynthesis (CM GT) which may be operative in these cell lines.…”
Section: Ir; 5 A9ht; 6 Yac-wa9ht; 7mentioning
confidence: 92%
“…The gangliosides are membrane constituents; however, very few membrane models have been proposed in which these compounds are considered (Lehninger, 1968) and we know of no report in which their synthesis is studied as part of a growing or turning-over membrane. A pathway for the biosynthesis of the carbohydrate chain of the gangliosides was proposed by Kaufman, Basu & Roseman (1966) and a different one by Kanfer, Blacklow, Warren & Brady (1964), Yip & Dain (1969) and Handa & Burton (1969). These pathways have been worked out from reactions occurring between water-soluble donors of glycosyl groups and lipid-soluble acceptors, catalysed by particulate preparations in a medium containing detergents which presumably altered the structures of the membranes.…”
mentioning
confidence: 99%
“…Asialo-GM 1 is then catalyzed to GMlb by a sialyltransferase. The enzymes involved in the formation of asialo-GM2 and asialo-GM1 were present in the nonadehsive rat ascites hepatoma cells (13) and in brain tissue (7,14). Therefore, the brain tissue and the nonadhesive rat ascites hepatoma ceils have similar enzymic components for the biosynthesis of GM 1 b in vivo.…”
Section: Discussionmentioning
confidence: 97%
“…Although the natural occurrence of this novel monosialoganglioside has yet to be proven in brain tissue, the dramatic accumulation of its proposed precursor, asialo-GM1, from patients afflicted with generalized gangliosidoses (10) and in nonadhesive rat ascites hepatoma cells (11) suggests that the synthesis of GMlb in vivo is possible. A most recent demonstration of the natural occurrence of GM 1 b in nonadhesive rat ascites hepatoma cells (12) has added considerable weight to the in vivo operation of the asialoglycolipid pathway for ganglioside biosynthesis originally proposed by Yip and Dain (7). The asialoglycolipid pathway involves the stepwise synthesis of the glycolipid precursors, dihexosylceramide (GL-2a), asialo-GM2 and asialo-GM1, from glucosylceramide by 3 glycosyltransferases.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation